Augmented Reality Solutions by Utilizing Mobile Technology for Enhanced Skill Development - Muhamad Arpan; Ambiyar; Ridwan; Auliana Nasution; Rifdarmon, (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study aimed to identify the effectiveness of the peer tutorial project learning model assisted by augmented reality (AR) in improving students’ 21st-century skills. The focus of the study was to describe the improvement in students’ skills taught using the AR-assisted project and peer tutoring-based learning (PPTBL) model, with an emphasis on four main abilities: critical thinking, creativity, collaboration, and communication. This study involved a comparison between a control group and an experimental group to measure the effectiveness of the learning model. The study results showed that the average critical thinking skills reached 81%, creativity 77%, collaboration 73%, and communication 74%. Data analysis showed that the hypothesis stating that there was a significant difference in 4C skills between students who study with the AR-assisted PPTBL model and those who study with the conventional learning model was accepted at a significance level of 5% (0.05). These findings were expected to make a significant contribution to the development of innovative learning methods that can be widely applied in higher education institutions.